Applying the ex turpi causa principle in tort actions - Todd, Stephen (Sweet & Maxwell, 2014)
An appropriate basis for denying the recovery of damages in tort on the ground that the plaintiff has been guilty of illegal wrongdoing has for long been a matter of debate in the common law courts. We can find a number of different justifications in the cases, with significant contributions being made by the House of Lords and the UK Supreme Court, the High Court of Australia, and the Supreme Court of Canada. The article examines the various arguments, makes suggestions as to what is helpful and what is not, and concludes by identifying the key questions to ask in any case where the illegality issue is raised.